Control synthesis for polynomial discrete-time systems under input constraints via delayed-state Lyapunov functions - Pitarch, J.L.; Sala, A.; Lauber, J.; Guerra, T.M. (International journal of systems science, 2016)
This paper presents a discrete-time control design methodology for input-saturating systems using a Lyapunov function with dependence on present and past states. The approach is used to bypass the usual difficulty with full polynomial Lyapunov functions of expressing the problem in a convex way. Also polynomial controllers are allowed to depend on both present and past states. Furthermore, by considering saturation limits on the control action, the information about the relationship between the present and past states is introduced via Positivstellensatz multipliers. Sum-of-squares techniques and available semi-definite programming (SDP) software are used in order to find the controller.